Analisis Hubungan Smartphone Addiction, Kecemasan, dan Stres Terhadap Kejadian Insomnia pada Mahasiswa Program Studi Kesehatan Masyarakat Universitas Nusa Cendana Kupang - Yurinus L. Radja; Ribka Limbu; Eryc Z. Haba Bunga; Pius Weraman (SEHATMAS: Jurnal Ilmiah Kesehatan Masyarakat, 2024)
Insomnia, as a sleep disorder characterized by the inability to achieve quality sleep, is often experienced by university students, with symptoms such as short sleep duration, difficulty falling asleep, and a lack of freshness upon waking up. This condition has a broad impact on the physical, emotional, and social health of students. This study aims to determine the relationship between smartphone addiction, anxiety, and stress with the incidence of insomnia among students of the Public Health Study Program at Universitas Nusa Cendana. This research used a cross-sectional design with an analytical survey method. The sample consisted of 66 students, selected using simple random sampling, with a significance level of α = 0.05. The results showed a significant relationship between smartphone addiction (p = 0.000), anxiety (p = 0.001), and stress (p = 0.001) with the incidence of insomnia. In conclusion, smartphone addiction, anxiety, and stress affect the students' sleep quality. The implications of this research highlight the importance of developing interventions to reduce smartphone addiction, as well as managing stress and anxiety among students to improve their sleep quality and well-being. The recommendations proposed include encouraging students to use smartphones more wisely, regulate their sleep patterns, exercise regularly, and strengthen social relationships to mitigate the negative impacts of smartphone addiction and stress.